Morphogenesis and mechanical properties of Bacillus amyloliquefaciens biofilms: a comparative study of rough and smooth morphotypes - Emmanuelle Baudu; Eric Raspaud; Catherine Fontagné-Faucher; Yassine Nait Chabane; Claire-Emmanuelle Marcato-Romain (Current Research in Microbial Sciences)
Bacillus amyloliquefaciens, a Gram-positive, endospore-forming bacterium, is ubiquitously found in diverse environments. Its resilience in harsh conditions and biofilm-forming capabilities make it a promising candidate for various agricultural applications. B. amyloliquefaciens can also colonize the air-liquid interface by producing pellicles. Despite its potential, the characterization of B. amyloliquefaciens biofilms remains underexplored. We investigated colony expansion and pellicle formation kinetic, followed by an analysis of the mechanical properties of the latter. This work focused on B. amyloliquefaciens strain L-17, which produced two morphotypes on agar plate: 1) a rough (R) morphotype exhibiting quick colony expansion and 2) a smooth (S) morphotype with a slower but extended colony expansion. The morphogenesis model of pellicle formation proposed in the literature for Bacillus subtilis was applicable to B. amyloliquefaciens, with few modifications for the smooth morphotype, which needed a longer period to spread over the surface. Mature pellicles were visually homogeneous and heterogeneous for R and S, respectively. Surprisingly, (i) their deformability by stretching was heterogeneous for the former and homogeneous for the latter; (ii) R produced a stiff pellicle whereas the entire smooth pellicle showed an elastic response.Taken together, results of this study confirmed that the existence of two distinct morphotypes within the same strain offers a unique opportunity to study the diversity of behaviors in B. amyloliquefaciens, providing insights into its potential applications in agriculture and beyond. Moreover, they led to the hypothesis that surfactant production and flagella expression are differentiating factors between both morphotypes.